The Positive Influence of Chinese Culture on Employees' Motivation and Retention: the P&G Case - Chen, Yu (2008)
In terms of the effect of Chinese culture on HRM of MNCs in China, a large amount of existing literature focuses on the negative aspects. On the basis of assuming that the advantages of Chinese culture can be integrated into HRM practices. This dissertation explores how some of Chinese traditional values play a positive role on Chinese employees' motivation and retention. These effects may be not possible achieved by classic Western HRM models and theories.